Activity of the Working Group on Enforced or Involuntary Disappearances of the United Nations Human Rights Council - Hryshko, L. M. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article reveals the work of the Working Group on Enforced or Involuntary Disappearances of the Human Rights Council, the oldest existing mechanism. The author gives a general description of the legal basis of the activity of this mechanism and discloses his work in the field of cases of violent disappearances of persons from the moment of their foundation. The article reveals the role of the Working Group on Enforced or Involuntary Disappearance in the adoption of important international instruments in the area of prevention of enforced or involuntary disappearances of people. The author concludes that the activity of this mechanism is aimed at establishing the fate or location of a person, regardless of the conditions and the term that has expired since the disappearance of the person.